Biology and Management of Ragweed Parthenium (Parthenium hysterophorous L.) in Ornamental Crop Production - Debalina Saha; Chris Marble; Robert H. Stamps; Shawn Steed; Nathan S. Boyd (EDIS)
This 6-page fact sheet provides an overview of Ragweed Parthenium, Parthenium hysterophorous L, including a species description and information on how to manage ragweed parthenium culturally, physically, and chemically. Written by Debalina Saha, Chris Marble, Robert H. Stamps, Shawn Steed, and Nathan S. Boyd, and published by the Environmental Horticulture Department, July 2016.